Perancangan UI/UX Aplikasi Portal Informasi dan Pendaftaran Turnamen E-Sports - Juniarto Christiawan Hartono; Nina Setiyawati (STMIK Banjarbaru, 2023)
E-sports are growing rapidly and there are more and more enthusiasts. Some players with a competitive spirit want to participate in a lot of tournaments, more and more people also want to organise tournaments. However, many players find it difficult to find information and register for e-sports tournaments, which is directly proportional to tournament organizers who often find it difficult to get participants. Therefore, the authors created a solution by designing a UI/UX design for a web-based application called POG (Portal of Gamers) which produces a prototype application interaction. The results of this design are expected to be a reference for developing applications that connect tournament organizers and players in organizing e-sports tournaments or competitions. The design method used in this research is Design Thinking. This method has 5 stages, namely empathize, define, ideate, prototype, and test. Usability test with the SEQ method, got a score of 6.67, which means that the Portal of Gamers can make it easy for players and organizers to support e-sports tournaments.Keywords: E-Sports Tournament; User interface; User experience; Design Thinking; Prototype AbstrakE-sports berkembang dengan pesat dan semakin banyak peminatnya. Sebagian pemain yang berjiwa kompetitif ingin mengikuti banyak turnamen, dan banyak juga orang yang ingin menyelenggarakan turnamen. Namun, banyak pemain yang merasa kesulitan mencari informasi dan melakukan pendaftaran turnamen e-sports, hal ini berbanding lurus dengan para penyelenggara turnamen yang sering kali sulit untuk mendapatkan peserta. Karena itu, penulis menciptakan solusi dengan merancang desain UI/UX aplikasi berbasis web yang bernama POG (Portal of Gamers) yang menghasilkan sebuah interaksi aplikasi prototype. Hasil rancangan ini diharapkan bisa menjadi acuan untuk pembangunan aplikasi yang menghubungkan penyelenggara turnamen dan juga pemain dalam penyelenggaraan turnamen atau kompetisi e-sports. Metode perancangan yang digunakan dalam penelitian ini adalah Design Thinking. Metode ini memiliki 5 tahapan yaitu emphatize, define, ideate, prototype, test. Pengujian usability dengan metode SEQ mendapatkan skor 6.67 yang artinya Portal of Gamers dapat memberikan kemudahan terhadap pemain dan penyelenggara untuk mendukung diselenggarakannya turnamen e-sports.